Wildflower strips in polytunnel cherry orchard alleyways support pest regulation services but do not counteract edge effects on pollination services - Mateos-Fierro, Zeus; Garratt, Michael P. D.; Fountain, Michelle T.; Ashbrook, Kate; Westbury, Duncan B. (Frontiers in Sustainable Food Systems, 2024)
Sweet cherry (Prunus avium) production relies on modern growing practices like polytunnel coverings to improve yields but this may interrupt arthropod-mediated ecosystem services. The distribution of beneficial arthropods (natural enemies and flower visitors) and the ecosystem services they provide may be affected under polytunnel systems, especially at orchard edges. Across 10 commercial cherry orchards grown in polytunnels, we explored how wildflower strips mitigated edge effects on beneficial arthropods and pest regulation and pollination services. In each orchard, we established a standard wildflower strip (SWS; single cut at the end of the season) and an actively managed wildflower strip (AMWS; regularly cut at 20 cm height) between tree rows and compared this to a conventional control strip (CS). We recorded natural enemies in alleyways and cherry trees post-cherry anthesis (flowering) and flower visitors during and post-cherry anthesis at different distances from the orchard edge (2017–2019). In 2019, we deployed insect prey bait cards in trees to measure pest regulation services and recorded fruit quality (2017–2019) and fruit set (2018–2019) to measure pollination services. Distance from the orchard edge did not affect natural enemy density or diversity in any year or under any alleyway treatment, but pest regulation services decreased towards orchard centres with CS (by 33.0% reduction). Flower visitor density (−34% individuals) and diversity declined with distance from the edge during cherry anthesis. For post-cherry anthesis, marginal negative edge effects were observed for flower visitor density and diversity and behaviour. Overall, fruit set decreased towards the orchard centre while fruit quality increased. Our results suggest that wildflower strips are an effective tool to mitigate edge effects on pest regulation services but have limited effects on flower visitors and pollination.